High-sensitivity detection of copper ions in water via cellulose nanomaterial nano-antennas and DFT studies - Arwa Alharbi; Abdullah A.A. Sari; Ali H. Alessa; Razan M. Snari; Hatun H. Alsharief; Ibrahim S.S. Alatawi; E.F.M. El-Zaidia; Nashwa M. El-Metwaly (Chemical Engineering Journal Advances)
The widespread occurrence of copper in water presents serious health hazards, requiring improvement of a method to monitor and remove copper ions in the field. In this study, a fresh approach is introduced that incorporates Cellulose Nanomaterials (CNMs) with a unique rod-like structure, offering a large surface area that is perfect for adsorbing cupral, a Cu(II) ion probe. By using this arrangement, toxic copper can be rapidly and visibly detected. Without any special tools, it's easy to see the color change from off-white to brown. The copper nano-antenna (CNA) has an impressively high sensitivity, detecting as low as 2.5 × 10–7 M through image analysis and 4.3 × 10–8 M with spectrophotometric methods. The values fall significantly below the WHO drinking water guidelines of 2 ppm. The CNA's ability to detect at low thresholds and be easily regenerated makes it an effective tool for initial water testing. According to the findings, the CNA could be a promising solution for enhancing safety in drinking water by allowing real-time visualization of copper ions, with only 5 mg required for measurements. Computational analysis has been conducted to study the structural properties of copper and its copper complex (Cu(CNA)2). There is a significant-close agreement between the theoretical and experimental results. The developed CNA material was tested in various environmental and real samples for detecting Cu2+ ions, especially in water and whitening cream samples showing the material application for real-world applications.